PERAN KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI MOTIVATOR DALAM MENINGKATKAN BUDAYA KERJA - Sumiati; Riyan Purwanto; Lilis Kholisoh Nuryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
School principals have a significant role to meet the needs of teachers as desired with the aim of increasing the performance carried out by the teacher. This type of research is a literature review (literature review), with stages namely collecting relevant research literature, marking several important terms in the research, conducting an in-depth analysis of the literature that has been obtained by compiling discussions, drawing conclusions based on the results of the analysis. The conclusion of this study is the ability of the principal to motivate subordinates, in this case the teacher as an educator is very influential on his performance, the higher the motivational ability possessed by the principal, the higher the performance carried out by the teacher. The principal carries out his duties as a motivator by carrying out several strategies, namely: 1) the principal maintains and maintains the physical environment of the school. 2) Arrange a comfortable working atmosphere. 3) To maintain the work motivation of teachers, the principal maintains teacher discipline. 4) Appreciation must be given to everyone who has completed a job as well as teachers as an educator. 5) Providing learning resources is the obligation of the principal to support the teaching and learning process in the school and provide learning resources including motivational activities carried out by the principal.